ANALISIS YURIDIS ATAS PELAYANAN NOTARIS/PPAT KEPADA KLIENNYA DALAM HAL PEMBAYARAN PAJAK PENGHASILAN (PPH) DAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB). (STUDI DI KOTA MEDAN) - NOMI CHAIRAINI TARIGAN (PREMISE LAW JURNAL, 2017)
ABSTRACT In accomplishing his job, a Notary/PPAT not only comply with Law but also provides services which support his job; for example, before making a Land Title Transfer Certificate, he has to ask his clients to pay the required PPh and BPHTB. The research used prescriptive method to find legal provisions, legal principles, and legal doctrines to answer the research problems. The aim of the research was to describe, explain, and analyze general legal theories and legal provisions on PPh and BPHTB so that a Notary/PPAT’s services for his clients in paying PPh and BPHTB could be obtained. The services of a Notary/PPAT to his clients in paying PPh and BPHTB are not regulated in the prevailing legal provisions. Keywords: Services by a Notary/PPAT to his Clients.